Combined Microstructural and Electrical Characterization of Metallization Layers in Industrial Solar Cells. (April 2015) - Kumar, P.; Willsch, B.; Dürrschnabel, M.; Aabdin, Z.; Hoenig, R.; Peranio, N.; Clement, F.; Biro, D.; Eibl, O.
Abstract: Screen printed front side contacts of textured, mono-crystalline p-type silicon solar cells with n-type emitters were investigated. The different pastes (FSP1 and 2) and the different crystallographic orientations of the Si surfaces studied strongly affected the contact resistance. The microstructure of the contacts was analyzed in plan-view and cross-section by combined scanning and analytical transmission electron microscopy. A controlled grinding process rather than a chemical etching process was applied for the plan-view sample preparation. For textured cells processed with different pastes, pronounced differences were seen in the contact resistances (FSP1: efficiency 16.9% and contact resistance 20 mΩ cm 2, FSP2: 17.8% and < 5 mΩ cm 2 ). A discontinuous glass layer was found for FSP1 but a continuous glass layer was found for FSP2, yielding a smaller contact resistance. Glass layers contained (Si2 Pb)Ox as a main constituent but different mole fractions of Zn, Ti, P, and B as minor constituents, varying for the different pastes. Glass layers were up to 500 nm thick and revealed inhomogeneously distributed spherical Ag colloids 5-200 nm in size. Planar cells were also studied and served as model systems: planar 〈111〉 oriented Si surfaces yielded specifically lower contact resistance as compared to planar 〈100〉 orientation. Pyramidal Ag crystallites were only observed for 〈100〉 oriented Si surfaces not for 〈111〉 surfaces. Therefore, it is concluded that pyramidal Ag crystallites are not necessary for contacts yielding low contact resistance. Instead, lens shaped Ag precipitates together with a high density of Ag colloids in the glass layer yield low contact resistance, as found for <111> oriented Si surfaces. A percolative current path including charge transport via Ag colloids in the glass layer is proposed. For textured cells, in accordance with these results, pyramidal Ag crystallites were only observed at step edges of {111} faces or at the edges of the Si pyramids.